INVENTARISASI HEWAN INVETEBRATA PADA FILUM NEMATHELMINTHES - RAHMADINA RAHMADINA; FAJAR RENALDI (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2020)
This journal discusses the theme of the Nemthelminthes phylum. nemathelminthes is a phylum that was once used in the animal kingdom (Animalia). Its members include a variety of worms known as gilig worms: animals with long cylindrical bodies, even so long that the name 'Nemathelminthes' appears. Which means "threadworm" (from Greek). His body is not sprouting. in this phylum, there are two classes, nematodes and nematomorphs. Nematodes have been found in the muscles outside the cells and not epithelial cells. There are no cilia here. An independent living nematode has a compound mouth and several tools and tastes and eyes. Gilig worms that live parasites, their body structure is simpler. The digestive tract is more complete and precisely divided into regions such as the mouth, oral cavity, pharynx, esophagus, small intestine, rectum, and body structure. The larvae live parasites on the human body or arthopoda, and after adulthood these worms live freely in fresh water and sea water.